Inventory Cost Reduction with Economic Order Quantity for Filter Spare Part in Aircraft Filling Depot - Furtyfatimah, Atita; Istiningrum, Andian Ari; Sono (Jurnal Manajemen dan Organisasi, 2023)
Filter is one of the spare parts playing an important role in maintaining the quality of aviation fuel. Filter replacement is increasingly being carried out when the frequency of aviation fuel distribution is higher. Therefore, it is necessary to control the filter level of inventory. This research aimed to design filter ordering schemes by Economic Order Quantity (EOQ) and to reduce the inventory cost for filter in aircraft filling depot. This research was conducted in one of aircraft filling depot in Indonesia. The data regarding filter demand, lead time, ordering cost, and carrying cost were collected from the depot’s documents. Several steps were conducted to achieve the purposes of the research including classifying filter category by ABC method, calculating optimal order quantity, order frequency, safety stock, reorder point, and inventory cost. The inventory cost calculated by EOQ was then compared to the actual inventory cost incurred in the depot to determine the inventory cost reduction. The implementation of EOQ enabled the depot to reduce its inventory cost by Rp8.348.848,20 or there was a 73,22 percent inventory cost reduction.. The EOQ used in this research was adapted to the difficulties of the depot to predict the demand of filters. The probabilistic EOQ used in this research was expected to be the contribution from this research since this method tended to be used in the uncertainty condition. Based on this method, the safety stock was calculated as a way to reduce the uncertainty demand and the risk of filter shortage.